2016
DOI: 10.18203/2349-3291.ijcp20164585
|View full text |Cite
|
Sign up to set email alerts
|

Complication profile of scrub typhus and its association with total leucocyte count

Abstract: Background: Recent reports from several parts of India indicate that there is a resurgence of scrub typhus. There have been a few studies analysing the association of various complications of scrub typhus with leukocyte count. The objective of this study was to study the association of various complications of scrub typhus with leukocyte count in children.Methods: A prospective study done at SPMCHI, SMS Medical College, Jaipur from August 2014 to November 2014. 75 Scrub typhus positive children were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
2
2
1
Order By: Relevance
“…The lowest leucocyte count reported was 2750 cells/mm 3 and the highest WBC count was 28,910 with a mean WBC count of 12,316. Leucopenia associated with scrub typhus was found out as a risk factor for development of complicated scrub typhus as reported by Gupta et al 19 After completion of treatment, leukocytosis persisted in 5 children in the azithromycin group and 8 children in the doxycycline group, whereas leucopenia resolved in all children in both the groups. Such results on resolution of laboratory parameters following treatment have not been reported earlier.…”
Section: Discussionsupporting
confidence: 58%
“…The lowest leucocyte count reported was 2750 cells/mm 3 and the highest WBC count was 28,910 with a mean WBC count of 12,316. Leucopenia associated with scrub typhus was found out as a risk factor for development of complicated scrub typhus as reported by Gupta et al 19 After completion of treatment, leukocytosis persisted in 5 children in the azithromycin group and 8 children in the doxycycline group, whereas leucopenia resolved in all children in both the groups. Such results on resolution of laboratory parameters following treatment have not been reported earlier.…”
Section: Discussionsupporting
confidence: 58%
“…The median total blood leucocyte count (15 000) and blood lymphocyte count were significantly higher whereas the platelet count was significantly lower in scrub typhus. A higher total leucocyte count in scrub typhus is against the general belief that scrub typhus is associated with leucopenia, as reported from India 20,26 ; however, studies have reported leucocytosis similar to that in the present study. 17,25,27 Thrombocytopenia ranging from 44.7% to 92.3% was frequently described by other authors as well.…”
Section: Discussioncontrasting
confidence: 57%
“…All the finding are at per with the reports of other researchers, except reduced urine volume and arthralgia, which found lesser in this study than other authors. 16,25,[29][30][31] An Eschar, which is a pathognomonic sign of scrub typhus infection found in 44.56% cases in this study. Similar findings reported by many previous studies, and much higher occurrence of eschar reported by some other researchers.…”
Section: Discussionsupporting
confidence: 47%
“…Similar findings reported by many previous studies, and much higher occurrence of eschar reported by some other researchers. 6,16,25,29,[30][31][32][33] Hepatomegaly (89.73%), lymphadenopathy (78.23%), pallor (74.33%) and splenomegaly (67.55%) were the common findings in this study. Other studies reported varied occurrence of hepatomegaly (26%-98%) and splenomegaly (17%-88%).…”
Section: Discussionmentioning
confidence: 82%